Desenvolvimento de conversor de quatro quadrantes para aplicações em veículos elétricos - Simão, Leonardo Hayashida (2023)
In this work, a drive and speed control system for an electric motor was developed and analyzed with the aim of evaluating its feasibility for application in electric vehicles. The system consists of a H-bridge converter and a microcontroller, which were simulated and experimentally tested. The obtained results were satisfactory, demonstrating the capability of precise speed control of the motor according to the established theoretical parameters. Both the simulation and practical tests highlighted the efficient performance of the system, which was able to control the motor speed under different conditions, including variable load situations and changes in rotation direction. The analysis of speed and current graphs confirmed the appropriate behavior of the system, showcasing its adaptability to load variations. Based on these conclusions, it can be stated that the proposed control system is viable for use in electric vehicles, providing precise motor speed control. It is important to emphasize that this study represents an initial stage, leaving room for continuous improvement of the system, both in terms of more advanced control strategies and integration with other components of the electric vehicle. The widespread adoption of this system has the potential to significantly boost the use of electric vehicles, thanks to its popularity, low cost, and high efficiency. This, in turn, contributes to a more sustainable and environmentally conscious future.